Assessment, life circumstances, curriculum and skills: Barriers and enablers to student mental wellbeing in distance learning - Lister, Kate; Andrews, Kyle; Buxton, Jo; Douce, Chris; Seale, Jane (Frontiers in Psychology, 2023)
Student mental wellbeing is increasingly a priority for universities, and this is particularly critical in a distance learning context. Studies have found that studying, academic pressure, university culture and systems can affect students’ mental health. There are increasing calls for universities to take a compassionate, holistic approach to supporting student wellbeing, and identify the barriers that are created by university cultures, systems, pedagogies, curricula, tuition and assessment practices. This study aimed to identify barriers and enablers to student mental wellbeing in distance learning, and students’ recommendations for changes to be made. Using a student survey (N = 584), we identified that assessment and life circumstances were the most significant barriers, while the greatest enablers were building study skills, the people in students’ lives, and curriculum and module content. The study revealed significant demographic differences in how students experience barriers and enablers, and how likely they feel they are to benefit from solutions. Students with disclosed mental health difficulties were consistently more likely to experience barriers than students without a disclosure, while enablers were experienced by all demographic groups. The study concludes that assessment should be prioritised as an area for action.